Optimizing Cabbage Cultivation in Paddy-Converted Fields Using Discarded Coir Substrates and Controlled Irrigation - Xin Wang; Yongjae Lee; To Kang; Jongseok Park (Agronomy)
This study aimed to reuse discarded coir substrates and optimize irrigation as a low-cost solution for addressing waterlogging in paddy-converted farmland. We employed a 2 × 4 factorial design, with two cultivation methods consisting of paddy soil (PS) and coir substrates (CS), and four irrigation levels (IL) set as 140% crop evapotranspiration (ETc140), 100% ETc (ETc100), 60% ETc (ETc60), and non-irrigated control (ETc0). We evaluated the growth and physiological characteristics of cabbage (Brassica oleracea L. var. Capitata), including the outer leaf growth, yield components, water use efficiency (WUE), photosynthetic parameters, chlorophyll content, proline content, malondialdehyde (MDA) content, and glucosinolates (GLs) content. The results indicated that the interaction between the CS and IL significantly improved cabbage growth, photosynthetic activity, and stress resistance compared with PS. Notably, when CS was combined with ETc100 and ETc60 irrigation levels, cabbage exhibited optimal growth parameters, and CS-ETc60 achieved the highest WUE. This study indicated that using discarded coir substrates combined with appropriate irrigation levels offers an effective and low-cost solution for mitigating waterlogging problems.